Mises en scène du pouvoir et enjeux statutaires chez les jeunes Palestiniens réfugiés (Liban) - Agnès Gharbi Mesmar (Ateliers d'Anthropologie)
Based on an ethnography written between 2005 and 2006 in a centre run by the NGO El Markez in the Nahr el-Barid Palestinian refugee camp (northern Lebanon), this article explores issues of power, status and reputation faced by youths who must build a future in an extremely difficult economic context. The first part explains the context of Palestinian refugee marginalisation in Lebanon, and how NGOs have developed as training organisations and important cultural and economic resources, and also introduces the organisation El Markez, its mission and the relative positions of its managers. Then the core of the article is dedicated to an analysis of a testing situation between the centre’s various protagonists: the exposure of the manager’s right-hand man, who was caught flirting with a visiting French woman. The consequences of the affair are carefully analysed, each of them based on a relatively formalised presentation (of how to “open” and “close” problems) characteristic of the political game in Middle East. This study shows how Lebanon’s young Palestinians learn politics, how this training period builds reputations and, finally, the resources that make it possible to settle them or, contrarily, transform them.